A review on insulation materials for energy conservation in buildings - Aditya L.; Mahlia T.M.I.; Rismanchi B.; Ng H.M.; Hasan M.H.; Metselaar H.S.C.; Muraza O.; Aditiya H.B. (Elsevier Ltd, 2023)
Air conditioning; Emission control; Energy conservation; Energy efficiency; Energy utilization; Historic preservation; Insulating materials; Life cycle; Permafrost; Thermal comfort; Efficient technology; Emissions reduction; Energy cost; Energy efficient; In-buildings; Insulation materials; Life cycle analysis; Residential sectors; Thermal insulation